Molecular dynamics and minigene assay of new splicing variant c.4298-20T>A of COL4A5 gene that cause Alport syndrome - Liang, Lei; Wu, Haotian; Cai, Zeyu; Zhao, Jianrong (Frontiers in Genetics, 2023)
Alport syndrome (AS) is a progressive hereditary kidney disease characterized by hearing loss and ocular abnormalities. According to the mode of inheritance, AS has three subtypes: X-linked (XLAS), autosomal recessive (ARAS), and autosomal dominant (ADAS). XLAS is caused by a pathogenic variant in COL4A5 gene encoding type IV collagen (Col-IV) α5 chain, while ADAS and ARAS were consequences of a variant in COL4A3 and COL4A4 genes that encode Col-IV α3 and α4 chains, respectively. Usually, diagnosis of AS requires hereditary or pathological assessment. Splice variants are hard to be determined as pathogenic or non-pathogentic based on the results of gene sequencing. This study focused on a new splice variant in COL4A5 gene, termed c.4298-20T>A, to analyze its authenticity and damaged α5 chain. In vitro minigene splicing assay was applied to investigate the effect of the new splice variant, c.4298-20T>A, on COL4A5 mRNA synthesis. Mo-lecular dynamics method was used to predict the capability of responsible α5(IV) to form a triple helix. The intron 46 of COL4A5 mRNA retained 18 bp, resulting in insertion of 6 amino acids behind the amino acid at position 1433 of α5(IV). As a consequence, the stability of α5(IV) sec-ondary structure was impaired, probably leading to unusual configuration of α345(IV). Usually, the splice variant in COL4A5 gene can lead to phenotypes of XLAS, and the effect is associated with the extent of splicing. The patient reported here carried a c.4298-20T>A splice variant in COL4A5 gene, and AS was highly suspected based on the pathological results. However, the patient did not manifest any ocular or ear abnormalities. Thus, c.4298-20T>A in COL4A5 gene is a new patho-genetic splice variant of XLAS that results in mild phenotypes.